2021
DOI: 10.1002/asi.24458
|View full text |Cite
|
Sign up to set email alerts
|

How is science clicked on Twitter? Click metrics for Bitly short links to scientific publications

Abstract: To provide some context for the potential engagement behavior of Twitter users around science, this article investigates how Bitly short links to scientific publications embedded in scholarly Twitter mentions are clicked on Twitter. Based on the click metrics of over 1.1 million Bitly short links referring to Web of Science (WoS) publications, our results show that around 49.5% of them were not clicked by Twitter users. For those Bitly short links with clicks from Twitter, the majority of their Twitter clicks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Mohammadi et al (2018) surveyed the motivations behind users' liking and retweeting behaviors in scientific contexts and reported that most survey respondents liked a tweet to "inform the authors that their tweets were interesting" and retweeted for the sake of disseminating the tweets. Based on the click metrics data provided by Bitly for its generated short links, Fang et al (2021) analyzed the click rates on Twitter of short links referring to scientific papers and concluded that nearly half of the studied scholarly short links were not clicked by Twitter users at all.…”
Section: User Engagement Behaviors Around Scholarly Tweetsmentioning
confidence: 99%
“…Mohammadi et al (2018) surveyed the motivations behind users' liking and retweeting behaviors in scientific contexts and reported that most survey respondents liked a tweet to "inform the authors that their tweets were interesting" and retweeted for the sake of disseminating the tweets. Based on the click metrics data provided by Bitly for its generated short links, Fang et al (2021) analyzed the click rates on Twitter of short links referring to scientific papers and concluded that nearly half of the studied scholarly short links were not clicked by Twitter users at all.…”
Section: User Engagement Behaviors Around Scholarly Tweetsmentioning
confidence: 99%
“…Even more strikingly, this modest reward pales in terms of costs/benefits when compared to simply omitting descriptors from the title. This is hardly surprising given the current landscape of ever-increasing new articles (59), fast and short communication [e.g., advertising through tweets; (60)], and the decreasing attention span of readers (61).…”
Section: Discussionmentioning
confidence: 99%
“…Chaining in this manner requires scientists to maintain the relevance and coherence between papers as their number grows exponentially. The second kind leverages a different type of network, which is social in nature, to support serendipitous sharing and finding of recommendations on social media platforms such as Twitter [37,55,63,81,114] or cold-emailing high-profile experts in an outside field to receive valuable bibliography [30,89,90,115].…”
Section: Related Work 21 Exploratory Search Needs In Scholarly Recomm...mentioning
confidence: 99%